Pengelolaan Pembelajaran Ipa Berbasis Masalah Di Sdn 1 Genengsari Toroh Grobogan - Wahyuningsih, Tri, Prof. Dr. Sutama, M.Pd, Dr. Maryadi, M.A (2016)
Tri Wahyuningsih. Q. 100 140 175. Problem-Based Learning Management Science at SDN 1 Genengsari Toroh- Grobogan. Thesis Graduate School of Muhammadiyah University of Surakarta in 2016 This study aims to describe the management of problem-based learning science at SDN 1 Genengsari Toroh-Grobogan. Then describe the implementation of problem-based learning science at SDN 1 Genengsari Toroh-Grobogan. And describe the problem-based curriculum evaluation IPA in SDN I Genengsari Toroh - Grobogan. This type of research is qualitative research design using an ethnographic approach. Problems found is, how planning, pelakasanan and evaluation of problembased learning science at SDN 1 Genengsari Toroh-Grobogan. The results showed that, (1) Planning Problem Based learning science at SDN 1 Genengsari Toroh- Grobogan. Planning Problem Based learning science management at SDN 1 Genengsari Grobogan, starting with the preparation of the RPP which refers to the standard of competence and basic competencies in the curriculum. (2) Implementation of Problem Based Learning science at SDN 1 Genengsari Toroh- Grobogan. Implementation of learning with their approaches to management of the science lesson plan, will make it easy for teachers to implement the implementation of learning in the classroom so that learning objectives achieved. (3) evaluation of Constraints management and science learning Problem Based at SDN 1 Genengsari Toroh-Grobogan. Evaluation study conducted before the lesson begins, at the time of the learning process and after the study is completed. In one semester, the teacher provides daily test of at least 2 times a month. Problem is made in the form of essays. Limited supply of props, media and students' own understanding of the problem will contribute into obstacles that must be faced in the management of learning. Keywords: problem-based, learning management, IPA